Pelaksanaan Penyuluhan Peranan Kunjungan Rumah (Home Care) tentang Kebutuhan Dasar Nifas pada Ibu post partum dengan Sectio Caesaria (SC) di Dusun Lepang, Kelurahan Padangsambian, Denpasar Barat - Ni Ketut Ayu Sugiartini (Politeknik Piksi Ganesha Indonesia, 2022)
The purpose of this community service is provide education to postpartum mothers about the basic needs of the puerperium including personal hygiene, elimination. The method used is counseling on basic needs during the puerperium that must be met such as eating and drinking, elimination, personal hygiene, vital sign examination, breast care, wound care so that later the mother is able to fulfill independently. Participants in this service program are postpartum mothers in Lepang Hamlet, Padangsambian Village, West Denpasar. It is hoped that after being given this counseling it can increase the knowledge and understanding of postpartum mothers about the basic needs of the postpartum period and be able to fulfill them independently.